(untitled) (UNIZIK Journal of STM Education, 2021)
This research was an effort to determine the relative effectiveness of analogy and concept maps instructional strategies on senior secondary two (SS2) students academic achievement in chemistry in Njikoka/Dunukofia Local Government Area (LGA) of Anambra State. The study was guided by three research questions and three null hypothesis tested at 0.05 alpha level. The study adopted a non equivalent pretest posttest control group quasi-experimental design involving two treatment groups. The sample comprised 55 SS2 students that offer chemistry who were drawn from two co-educational schools out of the 11 co-educational secondary schools using two-stage sampling procedure. The instrument for data collection was Chemistry Achievement Test (CAT). The CAT was validated by three experts and two secondary school chemistry teachers. The reliability coefficient of 0.79 was obtained using Kuder-Richardson formula (K-R 20). The CAT was administered as pretest for both experimental groups followed by a posttest after treatment was given using analogy and concept maps lesson plans. For data analysis, the pretest and posttest scores of the Chemistry students were used. Analysis of the data using the Mean, S.D and ANCOVA showed among others that there was no significant difference between the mean achievement scores of chemistry students taught using analogy instructional strategy when compared with those taught with concept maps instructional strategy. This means that none of the strategies was superior to the other. The result of the study equally showed no significant difference between the mean achievement scores of male students when compared with that of their female counterparts for both strategies. Consequently, it was recommended that since both strategies showed no significant difference in their effectiveness on students’ academic achievement in chemistry, teachers should adopt the use of both strategies in teaching of chemistry for enhanced achievement in the subject.